2005
DOI: 10.1073/pnas.0502761102
|View full text |Cite
|
Sign up to set email alerts
|

Sca-1 expression identifies stem cells in the proximal region of prostatic ducts with high capacity to reconstitute prostatic tissue

Abstract: We previously showed that prostatic stem cells are concentrated in the proximal regions of prostatic ducts. We now report that these stem cells can be purified from isolated proximal duct regions by virtue of their high expression of the cell surface protein stem cell antigen 1 (Sca-1). In an in vivo prostate reconstitution assay, the purified Sca-1-expressing cell population isolated from the proximal region of ducts was more effective in generating prostatic tissue than a comparable population of Sca-1-deple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
245
1
6

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 241 publications
(258 citation statements)
references
References 53 publications
6
245
1
6
Order By: Relevance
“…cells from the proximal region had even higher regenerative activity than the Sca-1-positive cells from the intermediate and distal regions (Burger et al 2005). Using 7AAD-staining, DNA-staining, and pyronin-Y RNAstaining techniques, we have shown that the Sca-1-positive cell fraction is enriched for quiescent cells, as defined by low RNA and DNA staining (Xin et al 2005).…”
Section: Prostate Stem Cells and Cancer 495mentioning
confidence: 81%
See 2 more Smart Citations
“…cells from the proximal region had even higher regenerative activity than the Sca-1-positive cells from the intermediate and distal regions (Burger et al 2005). Using 7AAD-staining, DNA-staining, and pyronin-Y RNAstaining techniques, we have shown that the Sca-1-positive cell fraction is enriched for quiescent cells, as defined by low RNA and DNA staining (Xin et al 2005).…”
Section: Prostate Stem Cells and Cancer 495mentioning
confidence: 81%
“…Since then, populations enriched for stem cell activity have been isolated from many adult tissues using various magnetic bead and FACS techniques Stingl et al 2006;Corti et al 2007). We and other investigators first identified the glycosyl phosphatidylinositol-anchored cell surface protein Sca-1 as a marker that can enrich for prostate stem cell activity, using magnetic bead sorting methods combined with in vitro and in vivo readout assays (Burger et al 2005;Xin et al 2005). …”
Section: Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…This region has been identified as the site of the organ's repository of epithelial stem cells (4,5,23). As stem cells lie in a special niche that nourishes them and keeps them in a primitive state, the high vascularity may contribute to the formation of the niche.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has been published for normal prostate epithelial stem or progenitor cells in the human [18][19][20] and mouse prostate. [21][22][23][24][25] Mouse data suggest that the stem cell compartment lies towards the base of the ducts near where they join the urethra. [26][27][28] Prostate tissue can be reconstituted by embryonic stem cells.…”
mentioning
confidence: 99%